Philosophical Overview of “The Nightmare Teacher” Series - Anggun Purnomo Arbi; Umi Nur Hastuti (English Language and Literature in Education Journal, 2026)
Television series frequently function as popular media texts that implicitly and explicitly convey philosophical meanings; however, scholarly inquiry into the philosophical dimensions of Nightmare Teacher (2016) remains limited. This study aims to examine how philosophical ideas are represented and constructed within the narrative structure of the series. Employing a qualitative descriptive-analytic design, the research analyzes all episodes through close textual reading, focusing on narrative patterns, character development, dialogic elements, and symbolic representations. The findings indicate that the series embeds philosophical themes primarily through the consequences of students’ wishes within a surreal classroom setting, reflecting existentialist concerns such as freedom, choice, responsibility, and the anxiety of self-determination. Additionally, elements of moral philosophy and phenomenology emerge through the tension between illusion and reality, as characters confront the ethical implications of their desires and the authenticity of their identities. The discussion reveals that the teacher figure functions as an allegorical catalyst that exposes the fragility of human desires within a technologically mediated and consumer-oriented culture. Consequently, the series operates as a philosophical allegory that encourages critical self-awareness and reflective thinking among viewers. Overall, this study concludes that Nightmare Teacher possesses significant pedagogical potential as a medium for philosophical reflection, particularly for younger audiences navigating identity, ethics, and the complexities of contemporary digital life.